2020
DOI: 10.1108/jfc-12-2019-0170
|View full text |Cite
|
Sign up to set email alerts
|

Retaliatory effect on whistle blowing intentions: a study of Indian employees

Abstract: Purpose This paper attempts to find the essence of whistleblowing in organizational structures, to reflect on whistleblowing mechanism and the perception of whistleblowing in the working class of a country. Whistleblowing is exhibited as one of the quintessential elements of corporate governance to prevent or detect inundating corporate frauds. This study examines the whistleblowing intentions and its precursors with the knowledge of repercussions, in context of Indian employees. Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 61 publications
1
8
1
Order By: Relevance
“…For managers, including internal auditing, compliance and controllership, it is relevant to know the beliefs of individuals in order to outline the most appropriate whistleblower channels, define compliance processes that contemplate the expectations of employees, in addition to establishing the controls and mechanisms that encourage whistleblower practices (Ciasullo et al, 2017;Kanojia et al, 2020;Said et al, 2017). In the criminal investigation process, the research findings contribute by presenting subsidies for investigators in the conduct of witnesses and potential whistleblowers (Alexander, 2004;Teichmann, 2018;Yakubu & Dikwa, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For managers, including internal auditing, compliance and controllership, it is relevant to know the beliefs of individuals in order to outline the most appropriate whistleblower channels, define compliance processes that contemplate the expectations of employees, in addition to establishing the controls and mechanisms that encourage whistleblower practices (Ciasullo et al, 2017;Kanojia et al, 2020;Said et al, 2017). In the criminal investigation process, the research findings contribute by presenting subsidies for investigators in the conduct of witnesses and potential whistleblowers (Alexander, 2004;Teichmann, 2018;Yakubu & Dikwa, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, self-efficacy may have relations to the internal locus of control, which proposes that internal locus of control’s may see whistleblowing as a step they must take to control an activity they cannot sanction (Near and Miceli, 1985). An individual who has an internal locus of control “believes in self and is guided by self-control and beliefs” (Kanojia et al , 2020). Curtis and Taylor (2009) found that auditors are more likely to report when they have an internal locus of control.…”
Section: Competence/capabilitymentioning
confidence: 99%
“…Curtis and Taylor (2009) found that auditors are more likely to report when they have an internal locus of control. Kanojia et al (2020) provided evidence of the effect of internal locus of control on WBI. Their findings suggest that WBI with the knowledge of retaliatory effects are primarily encouraged in individuals possessing internal locus of control because such people are not easily influenced by external forces but by their own credence.…”
Section: Perceived Moral Intensitymentioning
confidence: 99%
“…With respect to our objectives of this review paper, we find that in the select literature various characteristics of corporate governance, rules and regulations directly or indirectly relate to the corporate frauds, misgovernance and mis-statement in the financial reporting of the corporations and barring a very few papers, there is lack of research on the advent/usage/usefulness of the forensic accounting or any fraud detection technique other than whistleblowing (Kanojia, et al, 2020;Rezaee, 2005). In-spite of valuable contributions provided by forensic accounting towards the prevention and detection of corporate frauds there are not much literature available on selected database related to corporate governance and forensic accounting which states that it should be the part of corporate routine exercise or can be added in the curriculum of the education system except a few (Bhasin, 2016;Dutta et.…”
Section: Discussionmentioning
confidence: 99%